Preoperative functional status is associated with discharge to nonhome in geriatric individuals. Issue 7 (29th March 2021) - Hung, Ya‐Ching; Wolf, Joshua H.; D'Adamo, Christopher R.; Demos, Jasmine; Katlic, Mark R.; Svoboda, Shane
Abstract: Introduction: Discharging older individuals to rehabilitation facilities is associated with adverse outcomes, including readmission or increased mortality rate. As preoperative functional status is an important factor impacting patient outcome, we hypothesized that this would be associated with patient disposition to nonhome locations. Materials and Methods: A retrospective analysis was performed using data from the 2013–2018 American College of Surgeons National Surgical Quality Improvement Program, including targeted variables from the Geriatric Pilot Project. Patients aged 65 and older in 33 institutions across the nation were included ( n  = 44, 219). Preoperative functional status was categorized as independent, partially dependent, and dependent. The primary outcome was home versus nonhome disposition. Nonhome was defined as rehabilitation facility and nursing home. Descriptive analyses were performed. Variables associated with postoperative discharge to nonhome were identified using logistic regression. Results: The largest percentage of operations was orthopedics (40.8%), followed by general surgery (29.2%) and vascular operations (10.0%). The majority of the patients were independent before operations (93.1% independent, 6% partially dependent, and 0.9% totally dependent). In regression analyses, patients who were partially dependent preoperatively had five times higher odds of discharging to nonhome, compared to patients who were independent (odds ratio [OR] 5.04, p  < 0.01). Similarly, patients who were totally dependent had 3.2 higher odds of discharging to nonhome than patients who were independent (OR 3.22, p  < 0.01). Conclusion: Better preoperative functional status is associated with patient discharge to home in older adults. Preoperative interventions aimed at improving functional status, such as prehabilitation, may be beneficial in improving patient outcomes.